Stability Analysis Of Two-Position Control System In Interacting Tanks Using Describing Function Method - Andi, Purwandito Tulus Asmoro (Universitas Nusa Putra, 2024)
In a water storage unit consisting of 3 interacting tanks, in its operation there will be problems if manual control is used, because if manual control is not optimal, then when filling water in the three tanks it will cause water overflow, which results in a lot of water being wasted. Two-position control, or